PENERAPAN PSIKOEDUKASI PENCEGAHAN PERNIKAHAN DINI DI KELURAHAN LEGOK - Yun Nina Ekawati; Marlita Andhika Rahman; Nofrans Eka Saputra; Annisa Andriani; Dessy Pramudiani (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2023)
ABSTRACT The increasing number of early marriages occurring in society has an impact on the low quality of the population, especially the welfare of young women. Community Service Objective: To provide knowledge about the effects of early marriage on children and adolescents. The method of this research was activities using psychoeducation methods for children and adolescents. This service is carried out for three months.Results of Community Service: Psychoeducation has been carried out for children who are expected to understand the impact of early marriage if it occurs at the age of children and adolescents through understanding the ten dimensions of marriage readiness—participants' pretest-posttest results. Most participants experienced an increase in knowledge before and after being given psychoeducation. Community service has also succeeded in providing counselling skills to participants, but some participants still need a lot of practice to improve their counselling skills. Conclusion This community service has taken place well through psychoeducational activities. Participants have understood the ten dimensions of marriage readiness and are expected to practice counselling skills that have been applied in community service.Keywords: Psychoeducation, Early Marriage, Children ABSTRAKMeningkatnya angka pernikahan dini yang terjadi dimasyarakat yang berdampak pada rendahnya kualitas kependudukan khususnya kesejahteraan perempuan muda. Tujuan Pengabdian Masyarakat yakni untuk memberikan pengetahuan mengenai dampak pernikahan dini pada anak-anak dan remaja. Kegiatan menggunakan metode psikoedukasi dan pelatihan konseling untuk anak dan remaja. Telah dilaksanakan psikoedukasi untuk anak-anak yang diharapkan mampu memahami dampak pernikahan dini jika terjadi pada usia anak-anak dan remaja melalui pemahaman 10 dimensi kesiapan pernikahan. Hasil pretest-postest peserta Sebagian besar peserta mengalami peningkatan pengetahuan sebelun dan sesudah diberikanya psikoedukasi. Pengabdian masyarakat juga berhasil memberikan keterampilan konseling pada peserta, namun Sebagian peserta masih perlu banyak latihan dalam meningkatkan keterampilan konseling tersebut. Kesimpulan pengabdian masyarakat ini telah berlangsung dengan baik melalui kegiatan psikoedukasi. Peserta telah memahami 10 dimensi kesiapan pernikahan dan diharapkan melatih keterampilan konseling yang telah diterapkan dalam pengabdian masyarakat tersebut.Kata kunci: Psikoedukasi, Pernikahan Dini, Anak